Factors Leading to Pregnancies in Stimulated Intrauterine Insemination Cycles and the Use of Consecutive Ejaculations Within a Small Clinic Environment - Bahadur, Gulam (J Obstet Gynaecol India, 2016)
INTRODUCTION: Understanding and improving IUI pregnancy rates has enormous global appeal and application. This pilot study goes one step further by utilising consecutive ejaculates from men with oligozoospermia and comparing with normozoospermic male group. MATERIALS AND METHODS: A retrospective analysis was performed on 117 IUI-stimulated treatment cycles in a small fertility clinic in North Middlesex University Hospitals Trust, UK, within a NHS setting. Risks of OHSS and multiple births are carefully controlled. RESULTS: In our cohort, several factors are associated with positive IUI pregnancies and these were: age of the woman, inseminating with ≥5 total progressive motile sperm; having ≥50 % Grade A sperm progression and having ≥1 follicle achieved with a realistic hMG dosage, hCG trigger and IUI of 29.7 h (2.5–38.4 h), with an endometrial thickness of 10.7 mm (6.6–13.4 mm). Bifollicular presence in at least half the cases along with hMG protocols added usefully to the pregnancy outcomes. CONCLUSIONS: The pregnancy rates per cycle were 19 and 23 % in the consecutive ejaculates and non-consecutive ejaculate groups, respectively, P = 0.59. For the whole cohort, the pregnancy rate was 20.51 % per cycle and 33.8 % per women. This approach if validated with large RCT will have universally beneficial effects.